A ética de Paul Ricoeur: prolongamento hermenêutico do legado husserliano - Silva, Bruno Fleck da (2023)
Paul Ricoeur's ethical thought is characterized by a fruitful dialogue with the various ethical traditions, particularly teleological and deontological, based on epistemic elements arising from his contact with phenomenology, hermeneutics, ontology, among other constitutive areas of philosophical knowledge. . The present doctoral study aims to examine Ricoeurian ethics, inferring the phenomenological assumptions that constitute it through a possible inheritance coming from the ethical thought of Edmund Husserl. This thesis is justified based on three points observed in Husserlian ethics: the criticism of objective morality as a starting point; the possibility of practical wisdom based on the imperative of choosing the best and the centrality of ethics based on notions of will and the person. Ricoeurian ethics is characterized by the need to move from morality to fundamental ethics resulting in the varied expressions of regional ethics, a movement called practical wisdom. As a constitutive moment of the self in ethical action, narrative identity is affirmed by the conviction that links person and promise based on ipseity and manifest attestation based on a phenomenology of capabilities. The phenomenological background present in this hermeneutic structure of Ricoeurian ethics highlights the singularity of a consciousness phenomenologically focused on the world and its problems in an ethically responsive attitude. Finally, it is evident that the relationship between will and ethical situations leads ipseity back to the essential of resolute production in a poetic order, which characterizes the specific movement of a phenomenological ethics augmented by hermeneutics, as well as highlighting the intrinsic relationship between phenomenology and hermeneutics in the epistemology inherent to the ethics of the French thinker.